Financial Sector Debt Bias - Luca, Oana (IMF Working Papers; Working Paper, 2016)
Most tax systems create a tax bias toward debt finance. Such debt bias increases leverage and may negatively affect financial stability. This paper models and estimates debt bias in the financial sector, and present novel estimates for investment banks and non-bank financial intermediaries such as finance and insurance companies. We find debt bias to be pervasive, explaining as much as 10 percent of total leverage for regular banks and 20 percent for investment banks, with the effects most pronounced before the global financial crisis. Going forward, debt bias is likely to once again gain prominence as a key driver of leverage decisions, underscoring the importance of policy reform at this juncture.